2016
DOI: 10.1111/fwb.12717
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour, predatory functional responses and trophic interactions of the invasive Chinese mitten crab (Eriocheir sinensis) and signal crayfish (Pacifastacus leniusculus)

Abstract: SUMMARY1. Freshwaters are subject to particularly high rates of species introductions; hence, invaders increasingly co-occur and may interact to enhance impacts on ecosystem structure and function. As trophic interactions are a key mechanism by which invaders influence communities, we used a combination of approaches to investigate the feeding preferences and community impacts of two globally invasive large benthic decapods that co-occur in freshwaters: the signal crayfish (Pacifastacus leniusculus) and Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
49
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 84 publications
(102 reference statements)
12
49
1
Order By: Relevance
“…Predicting and explaining predatory impacts of alien decapod Crustacea 2831 leniusculus also had a higher maximum feeding rate than A. pallipes on all prey items, in accord with previous studies using G. pulex as prey (Haddaway et al 2012;Rosewarne et al 2016) and the general pattern emerging from FR studies in invasion ecology (Dick et al 2017). However, this difference was only significant on chironomid prey, and differences were generally small in magnitude (up to 1.3 times higher in P. leniusculus) relative to the differences observed between E. sinensis and the two crayfish species.…”
Section: Pacifastacus Leniusculussupporting
confidence: 85%
See 4 more Smart Citations
“…Predicting and explaining predatory impacts of alien decapod Crustacea 2831 leniusculus also had a higher maximum feeding rate than A. pallipes on all prey items, in accord with previous studies using G. pulex as prey (Haddaway et al 2012;Rosewarne et al 2016) and the general pattern emerging from FR studies in invasion ecology (Dick et al 2017). However, this difference was only significant on chironomid prey, and differences were generally small in magnitude (up to 1.3 times higher in P. leniusculus) relative to the differences observed between E. sinensis and the two crayfish species.…”
Section: Pacifastacus Leniusculussupporting
confidence: 85%
“…Rosewarne et al (2016) reported that E. sinensis had a higher FR than P. leniusculus and A. pallipes. However, we demonstrate that relative impact of E. sinensis may be much greater than previously thought, with an attack coefficient up to 6.7 times, and maximum feeding rate up to 3.0 times, that of a similarly sized crayfish (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations